Designing a twin frequency control DC-DC buck converter using accurate load current sensing technique - Kok, Chiang Liang (2024)
In this paper, a buck DC-DC converter with the proposed twin frequency control scheme (TFCS) and accurate load current sensing (ALCS) was designed and implemented with 0.18 µm CMOS technology for a supply voltage ranging from 2.0 to 3.0 V, which is compatible with state-of-the-art batteries (NiCd/NiMH: 1.1–2 V, Li-Ion: 2.5–4.2 V). The proposed converter yields a peak efficiency of about 92.7% with a load current of 30 mA. Furthermore, it only occupies a silicon area of 1.3 mm2. The proposed buck converter is dedicated for smartphone applications whereby it spends most of its time in idle, low load conditions.